Body composition changes after one year in professional male ice hockey players - Stanzione, J. R.; Dardarian, N.; Volpe, S. L. (International Journal of Sports Medicine, 2020)
Body composition measurements remain one of the best objective ways to analyze tissue distribution in athletes. The purpose of this study was to establish an average body composition profile for professional male ice hockey players, assess the yearly fluctuations of body composition after a single season, and assess body composition changes among different positions. Body composition was measured using dual-energy X-ray absorptiometry in 36 professional male ice hockey players. Descriptive statistics were used to determine average values. A paired samples t-test was applied to determine differences over a one-year period. A one-way analysis of variance was used to determine differences between positions, at both time points. Alpha levels were set a priori at p<0.05. Significant increases were observed in percent body fat across time points for all positions (p=0.019). There were significant differences in percent body fat between positions played (p=0.012) after one year. We demonstrated that there was low variability among the different positions in professional male ice hockey players. Additionally, we observed how a single year minimally influences changes in body composition. More research is required to evaluate body composition in male ice hockey players.